Characterization of silver iodide-sodium iodide ice nuclei using chemical kinetic methodology - Blumenstein, Rochelle Rose, author; Department of Atmospheric Science, Colorado State University, publisher (Colorado State University. Libraries, 1985)
Ice nucleation by aerosol particles generated from combustion of acetone solutions of silver iodide and sodium iodide has been characterized in the CSU Isothermal Cloud Chamber using the techniques of chemical kinetics. The mechanism of ice nucleation has been found to be primarily condensation-freezing ice nucleation. Two separate mechanisms of ice nucleation have been observed. One mechanism, identified as condensation to droplets followed by freezing, occurs at water saturation and is a characteristically slow process, with a half life on the order of 10-30 minutes. The other mechanism, identified as condensation to aqueous embryos followed by freezing, occurs at water supersaturated conditions, is characteristically fast, requiring less than a minute for completion, and results in a higher yield of ice crystals than the slow mechanism. The mechanisms are dependent on temperature and water vapor concentration, respectively, and are independent of the liquid water content of the cloud. Contact of the aerosol particles with cloud droplets has also been observed at high liquid water contents to be a mechanism of ice nucleation by silver iodide-sodium iodide aerosol particles. The energy of activation for the slow mechanism of condensation to droplets followed by freezing has been found to be three times the latent heat of condensation of water. This is believed to be related to the extent of hydration of the silver iodide-sodium iodide complex. The mechanisms, rates, and yields observed in the laboratory are applied to a theoretical, physical and microphysical orographic cloud model to assess the ice nucleation characteristics of silver iodide-sodium iodide aerosol particles in the temporal and spatial scale of an orographic cloud. Three parameters have been found to control the extent and location of ice nucleation: 1) nucleation mechanism, 2) cloud temperature, and 3) wind speed. The slower mechanism of condensation to droplets followed by freezing, which occurs at slight water saturation, causes ice crystal production to be prolonged over time and space. Resulting precipitation can occur over large areas. The faster mechanism of condensation to aqueous embryos followed by freezing, which occurs in water supersaturated areas of the cloud, results in ice nucleation primarily within a zone of a few kilometers of the cloud. Precipitation would then occur in a limited area on the surface which would subsequently affect the targeting and analysis of seeding effects. Temperature influences the yield, or effectivity, and is most important for the fast mechanism. Wind speed controls the time available for nucleation. Application of laboratory determined rates and mechanisms to various cloud models can be an important tool in the development of the hypothesis, statistical design, and physical analysis of experiments and programs that utilize artificial ice nucleants for weather modification.
May 1985.
Keywords: Atmospheric nucleation; Ice nuclei